Caribbean Report 03-03-1999 - The British Broadcasting Corporation; Ransome, Debbie (correspondent); O'Connell, Paddy (correspondent); Singh, Rickey (interviewee); Brown, Gordon (interviewee); Richardson, Wakefield (correspondent); Hernandez, Jose Juan (interviewee); Greaves, Keith Stone (correspondent); Gifford, Adam (interviewee) (The British Broadcasting Corporation, 1999)
1. Headlines with anchor Debbie Ransome (00:28) 2. The US announced its decision to delay imposing punitive tariffs against selected European Union goods as part of its long running trade row. The World Trade Organization in Geneva is seeking more time to arbitrate. BBC New York business correspondent Paddy O’ Connell reports on the ongoing trade negotiations (00:29 - 02:06) 3. CARICOM leaders are scheduled to start an intercessional meeting in Suriname. Key items on the agenda for discussion include the political crisis in Haiti, World Trade Organization negotiations to end the banana trade dispute between the US and the European Union, crime in the region and the OECS. Journalist Rickey Singh discusses Caribbean relationship with the US, Europe, Latin America, South Africa and Japan (02:07 – 06:59) 4. The indebtedness and poverty crippling the economies of developing countries is being addressed by Great Britain. The British government announced a new campaign aimed at reducing these two major issues in developing countries. British Finance Minister Gordon Brown outlines a plan to reduce debt and increase aid from industrialised countries and international agencies (07:00 - 07:32) 5. British overseas territory Anguilla head to the polls to elect a new government. Sixteen candidates are campaigning for seven seats in the House of Assembly. Anguilla United Party headed by Chief Minister Hubert Hughes fielded two candidates and his coalition partner the Anguilla Democratic Party is fielding four candidates. Opposition Anguillan National Alliance is contesting six seats. There are four independent candidates. Correspondent Wakefield Richardson reports on the elections (07:33 - 09:45) 6. In Puerto Rico, one of the island’s major labour unions opposes the government’s decision to sell the state telephone company. President of the Independent Telephone Workers Union Jose Juan Hernandez discusses the sale of the company to an American based Texas consortium for three billion US dollars. Correspondent Keith ...